Womanhood and the media: Nigeria and the Arab World. (2011)
The concept of womanhood and mass media continues to undergo tremendous transformation especially in Africa and particular in Nigeria. Some of the most influencial factors responsible for this change among other things include economic, socio-cultural and political dynamics. This study, examines women and the media with examples from Nigeria and the Arab world; some facts and figures about women, media and the inherent implications. The researcher conclude that in the coming years, the number of women in media in Nigeria and Africa will undoubtedly grow, just as more men will become interested in writing on softer issues, presently associated with women alongside the stereotype.